Use of alginate/montmorillonite nanocomposites as drug delivery system for curcumin - Ahmed, Marwa Fathy (AUC Knowledge Fountain, 2015)
Curcumin (Cur.) is a well known traditional medicine due to its anti-inflammatory and antioxidant properties. Its pharmacological mechanism of action and safety have been extensively studied to investigate its use in clinical and therapeutic applications. However, its low water solubility and rapid metabolism are main obstacles. Different techniques were used to overcome the drawbacks of curcumin, with recent attention focusing on approaches based on nanotechnology. Clay-polymer nanocomposites are getting to play a role in nanoformulations for drug delivery. This is due to their improved rheological and mechanical properties, and controlled drug release characteristics compared to their individual components, clays and polymers. Alginate/ montmorillonite (MMT) nanocomposites are used as drug delivery system for a wide variety of drugs due to numerous advantages of both components such as the high loading capacity of MMT and the ability of alginate release encapsulated drugs in a controlled manner. Accordingly, this study aimed at the preparation of curcumin loaded alginate/MMT nanocomposites and the investigation of their release properties. Exfoliated MMT clay was first prepared by stirring the clay in an aqueous suspension for 4 hours, followed by filtration and drying at 70 °C. Exfoliation was confirmed by X-ray diffraction (XRD) and Fourier Transform infrared (FTIR) spectroscopy. Curcumin loaded MMT was then prepared by dispersing the exfoliated clay into an ethanoic curcumin solution. Different parameters were tested, namely stirring time, curcumin solution concentration and ratio of MMT to curcumin, in order to find out the maximum loading conditions. Stirring exfoliated MMT into curcumin solution of 1 mg/ml for 1 hour and in 5% W/V ratio was found to be the best condition for maximum loading (6.56 mg/g, corresponding to entrapment efficiency of 25.62 %). The hybrid sample (curcumin loaded MMT) was thus prepared. Visible spectrophotometric measurements of the curcumin solution were used to determine the amount of curcumin loaded by measuring the absorbance of curcumin solution before and after the dispersion of the clay. The hybrid sample was then encapsulated into alginate beads with different hybrid to alginate ratios (W/W) using the ionotropic technique. XRD and FTIR analysis were used for the characterization of the prepared hybrid and nanocomposites. They revealed the increase in the degree of clay exfoliation upon drug loading and encapsulation into the alginate beads and the loss of the crystalline nature of curcumin upon v adsorption onto the clay surface without any chemical interaction between the clay and curcumin. The release of curcumin from different alginate/MMT nanocomposites was studied in different biorelevent media: fast gastric (FaSSGF), fast intestinal (FaSSIF) and fed intestinal media (FeSSIF). The curcumin release in gastric media was negligible and this was attributed to its low solubility in these media and to the shrinkage of alginate beads in the acidic pH environment. Curcumin release in intestinal media was significantly higher and was found to be affected by both the feeding state and the ratio of hybrid to alginate. Increasing the hybrid to alginate ratio decreased the percentage of curcumin release because of the decrease of the swelling ratio of alginate due to the crosslinking effect of the clay. Consequently, the 1:20 (W/W) hybrid to alginate ratio nanocomposite sample (NC 1) showed the highest release percentage in both fast and fed intestinal media (71% in the FaSSIF and 15.5 % in the FeSSIF). On the other hand, the 1:2 (W/W) hybrid to alginate ratio nanocomposite sample (NC 4) demonstrated the lowest release percentage in both media (17.4% in FaSSIF and 6.6 % in FeSSIF). The feeding state played additional role in the percentage of curcumin released as it was found to affect both the pH and the concentration of the natural solubilizing components such as phospholipids and bile salts of the intestine. Accordingly, the percentage of curcumin released was higher in the fasting state than in the fed state due to the higher pH of the former media (88.4% in the FaSSIF and 16.6% in the FeSSIF for NC 1. Curcumin release in both intestinal media demonstrated different behaviors: in FaSSIF sustained release behavior was found to occur for 24 hours, while curcumin release reached a plateau by 8 hours in the FeSSIF. This study reveals the promising use of alginate/MMT nanocomposites as sustained release drug delivery system for curcumin through surface adsorption of curcumin onto the surface of exfoliated clay and encapsulation of the loaded clay into alginate beads. The release of curcumin would be hindered into the gastric environment and start into the intestine. For maximum and sustained release behavior a fasting state is preferred.